Pengembangan SDM dan Pelatihan Kewirausahaan Berbasis Potensi Lokal Pengolahan Susu Sapi Perah di Desa Mulyosari Pagerwojo Tulungagung - Muhammad Al Faruq; Siti Kalimah (LP3M IAIFA Kediri, 2020)
society must have more ability and proficiency not only to take a hand, but welfare is also needed one way by utilizing local potential, processing raw materials of potential regional results by conducting human resource training and the practice of making products and later marketed as an effort to increase income to help families improve people's living standards. Therefore, as a welfare effort, there was research with the theme of Human Resources Development and Entrepreneurship Training based on the local potential of dairy milk processing